Effect of Sodium Alginate Coating Incorporated with Epigallocatechin Gallate and Peanut Oil on Refrigerated Hilsa (Tenualosa ilisha) Chunk - Hossain, Onamika; Faridullah, Md.; Islam, Md. Reazul (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
Hilsa, the national fish of Bangladesh, is highly perishable despite its high nutritional value. Low-temperature preservation, salting, and synthetic preservatives are used to extend the shelf life of hilsa. Nowadays, researchers are searching for safer alternatives. Edible coatings are a safe and effective method for extending the shelf life of fish. This research aims to assess the efficacy of a sodium alginate-based edible coating enriched with the antioxidant and antimicrobial agent epigallocatechin gallate (EGCG) and peanut oil for preserving the quality and extending the shelf life of refrigerated hilsa fish chunks (HFC). In the experiment, HFC samples were divided into four treatment groups: T1 (sodium alginate, 2%), T2 (sodium alginate 2% with peanut oil 1%), T3 (sodium alginate 2%, peanut oi 1%, and EGCG 0.2%), and a control group (CON) treated with distilled water. Samples were stored at 4±1 °C and evaluated over 12 days for biochemical parameters, including pH, total volatile base nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS), and microbial counts on tryptic soy agar (TSA) and violet-red bile agar (VRB). Initial pH values (5.73±0.03 to 5.74±0.04) were not significantly different (p0.05), but T3 exhibited a significant increase by day 12 (6.54±0.04, p0.05). TVB-N levels showed that T3 remained within acceptable limits until day 9, while CON and T1 exceeded spoilage limits by day 6. TBARS values surpassed the oxidative rancidity threshold of 2 mg MDA/kg by day 6 in CON and day 9 in T1 and T2, while T3 remained acceptable until day 9. Sensory evaluation indicated that T3 maintained its quality longer than the other treatments. These findings suggest that sodium alginate coatings with EGCG and peanut oil effectively extend the shelf life of refrigerated HFC, offering a sustainable alternative to synthetic preservatives.